2020
DOI: 10.3390/en13010235
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Corrosion Methods for Bipolar Plates for High Temperature Polymer Electrolyte Membrane Fuel Cell Application

Abstract: In this work, different methods and electrochemical set-ups were investigated in order to study the corrosion behaviour of bipolar plates (BPP) for high temperature (HT) polymer electrolyte membrane fuel cell application. Using confocal and scanning electron microscopy, it was shown that chemical and electrochemical aging significantly increases surface roughness as well as morphology changes, confirming material degradation. Identical electrochemical corrosion behaviour was observed for both set-ups with typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The value of shunting currents is in the order of one to a tenth of mA/cm 2 , and it is dictated by geometrical profiles of channels for electrolyte distribution and electrolytes conductivity 26,27 . The selection of optimal channel configuration can mitigate this problem, resulting in the maximum shunt current value of 2 mA cm 2 or less 28 . Therefore, the same current density was chosen as a cutoff for the determination of electrochemical window stability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of shunting currents is in the order of one to a tenth of mA/cm 2 , and it is dictated by geometrical profiles of channels for electrolyte distribution and electrolytes conductivity 26,27 . The selection of optimal channel configuration can mitigate this problem, resulting in the maximum shunt current value of 2 mA cm 2 or less 28 . Therefore, the same current density was chosen as a cutoff for the determination of electrochemical window stability.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 The selection of optimal channel configuration can mitigate this problem, resulting in the maximum shunt current value of 2 mA cm 2 or less. 28 Therefore, the same current density was chosen as a cutoff for the determination of electrochemical window stability. Thus, the potential range at which the oxygen and hydrogen evolution currents were 2 mA/cm 2 was extracted.…”
Section: Electrochemical Potential Windowmentioning
confidence: 99%
“…These studies showed power losses due to MEA degradation in the form of membrane thinning or formation of pinholes, catalyst layer thinning and formation of cracks or even intrusion of GDL fibres (14)(15)(16). Carbon-based composite bipolar plates are prone to undergo corrosion and thus fail to ensure a proper functionality during critical conditions (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to commercial graphite PEMFC I , they show outstanding resistance to corrosion and favorable electrical and thermal conductivity. However, the low density, weak mechanical strength, material and processing cost restrict its usage [ 12 , 13 , 14 ]. Metal plate-based interconnectors are usually coated with various protective materials to enhance their corrosion resistance [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%